2004
DOI: 10.1080/02841860310017441
|View full text |Cite
|
Sign up to set email alerts
|

HER-2, EGFR, COX-2 Expression status correlated to microvessel density and survival in resected non-small cell lung cancer

Abstract: The incidence of lung cancer is increasing throughout the world and is the most common cause of cancer-related death. Early detection followed by surgery has a reasonable, curative potential, but 30-50% of patients experience relapses. The immunohistochemical expressions of HER-2, EGFR and COX-2 were investigated in 53 resected non-small cell lung carcinomas and correlated to microvessel density and clinical data. HER-2, EGFR and COX-2 overexpressions were demonstrated in 15%, 30% and 40% of the tumours, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 0 publications
1
28
1
1
Order By: Relevance
“…La positividad para este oncogen y el EGFR parece definir un subgrupo de tumores con un peor comportamiento y evolución 33 . Asimismo, este gen se correlaciona con la densidad de microvasos 34 y es responsable de la resistencia a ciertos fármacos 35 . Los carcinomas escamosos son más proliferativos que los adenocarcinomas, lo cual puede explicar una mayor agresividad y una mejor respuesta al tratamiento 36 .…”
Section: Discussionunclassified
“…La positividad para este oncogen y el EGFR parece definir un subgrupo de tumores con un peor comportamiento y evolución 33 . Asimismo, este gen se correlaciona con la densidad de microvasos 34 y es responsable de la resistencia a ciertos fármacos 35 . Los carcinomas escamosos son más proliferativos que los adenocarcinomas, lo cual puede explicar una mayor agresividad y una mejor respuesta al tratamiento 36 .…”
Section: Discussionunclassified
“…Several studies have shown EGFR associated with poor prognosis (12)(13)(14), whereas other trials have shown no prognostic association (15,16). In concordance with Suzuki et al (2), the disparity in reports of the EGFR as a prognostic factor may reflect differences in detection methods, reagents, assay, cut-off points and population characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen publications, published between 1999 and 2005, were eligible for the systematic review (Achiwa et al, 1999;Hosomi et al, 2000;Khuri et al, 2001;Brabender et al, 2002;Kim et al, 2003;Ab' Saber et al, 2004;Araki et al, 2004;Lu et al, 2004;Yamaguchi et al, 2004;Brattstrom et al, 2005;Laga et al, 2005;Marrogi et al, 2005;Richardson et al, 2005;Yuan et al, 2005). These publications concerned different cohorts of patients.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Among the 14 studies eligible for the systematic review, four (Hosomi et al, 2000;Ab' Saber et al, 2004;Brattstrom et al, 2005;Marrogi et al, 2005) were inevaluable for the meta-analysis owing to a lack of data in the publication, not allowing to calculate the individual HR and its variance.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%